Bivalirudin Versus Heparin Monotherapy in Elderly Patients With Myocardial Infarction: A Prespecified Subgroup Analysis of the VALIDATE-SWEDEHEART Trial. (April 2020) - Wester, Axel; Attar, Rubina; Mohammad, Moman A.; Isma, Nazim; James, Stefan; Omerovic, Elmir; Erlinge, David; Koul, Sasha
Abstract : Background: Elderly patients with acute myocardial infarction undergoing percutaneous coronary intervention are at increased risk of both ischemic and bleeding complications. The optimal anticoagulation strategy in these patients is uncertain. Therefore, we compared bivalirudin to heparin monotherapy in a contemporary cohort of such patients. Methods: A prespecified subgroup analysis of elderly patients with myocardial infarction (≥75 years) from the VALIDATE-SWEDEHEART trial (Bivalirudin Versus Heparin in ST-Segment and Non–ST-Segment Elevation Myocardial Infarction in Patients on Modern Antiplatelet Therapy in the Swedish Web System for Enhancement and Development of Evidence-Based Care in Heart Disease Evaluated According to Recommended Therapies Registry Trial) was performed. In the trial, patients were randomized to either bivalirudin or heparin monotherapy during percutaneous coronary intervention, with mandatory potent P2Y12 inhibition, routine radial artery access, and only bail-out glycoprotein IIb/IIIa inhibition. Kaplan-Meier event rates were assessed for the primary end point, consisting of a composite of all-cause death, myocardial reinfarction, or major bleeding, within 180 days. Results: The elderly (n=1592) had more than twice the risk of all events compared with younger patients (n=4406). Baseline and periprocedural characteristics were equal between bivalirudin (n=799) and heparin (n=793) treated patients ≥75 years. No differences were found in the elderly between bivalirudin and heparin monotherapy regarding the primary end point (180-day all-cause death, myocardial reinfarction, or major bleeding), the individual components of the primary end point, definite stent thrombosis, or stroke. Conclusions: In this prespecified subgroup analysis of the VALIDATE-SWEDEHEART trial, elderly patients with myocardial infarction had a highly increased risk of all events. However, no difference in outcomes could be observed with an anticoagulation strategy with either bivalirudin or heparin as monotherapy in this patient group. Abstract : Supplemental Digital Content is available in the text.